Fine structural changes of Rohu Labeo rohita) sperm after dilution with cryoprotectants - Gopalakrishnan, A; Ponniah, A G; Lal, Kuldeep K (Indian Journal of Fisheries, 2011)
Spermatozoa of rohu (Laheo rohita) were diluted in two cryodiluents and fine structural changes were investigated. Damages were observed in head, mid-piece and tail of about 51% spermatozoa immediately after dilution in one of the cryodiluents. After 10 minutes of equilibration period, the frequency of damaged sperms increased to 85%. The other diluent did not exhibit significant structural changes unlike the former one and nearly 60% sperms remained visibly intact even after 10 minutes of equilibration time. The present investigation points out (1) diluents inhibiting sperm motility alone need not always be ideal for a species and (2) usefulness of ultrastructural images offish sperms in determining the fertilizing ability of milt and in preliminary screening and selection of cryodiluents for deepfreezing programmes.